Effects Of T6 Heat Treatment With Double Solution Treatment On Microstructure, Hardness And Corrosion Resistance Of Cast Al-Si-Cu Alloy - Wiengmoon A.; Sukchot P.; Tareelap N.; Pearce J.T.H.; Chairuangsri T. (Archives of Metallurgy and Materials, 2015)
Effects of T6 heat treatment with double solution treatment on microstructure, hardness and corrosion resistance of a cast A319 (Al-4.93wt%Si-3.47wt%Cu) alloy were investigated. The T6 heat treatment comprised of the first solution treatment at 500±5°C for 8 h, the second solution treatment in the temperature range of 510 to 530±5°C for 2 h followed by water quenching (80°C), and artificial aging at 170°C for 24 h followed by water quenching (80°C). Microstructure of the alloy was studied by optical microscopy and electron microscopy, Rockwell hardness was measured, and corrosion resistance in 0.1 M NaCl aqueous solution was determined by a potentiodynamic technique. The results revealed that the T6 heat treatment with double solution treatment led to an improvement in corrosion resistance and comparable macrohardness as compared to those obtained from the case of single solution treatment. The second solution treatment at 520°C is the optimum leading to relatively low corrosion current density without substantial drawbacks on breakdown potential or the width of passive range.